Mathematical modeling and simulation: a tool for crop protection - Durán-Peralta, Elisa; Acuayte-Valdes, Erik; Acuayte-Valdes, María del Consuelo; Juan Carlos; López-Cruz, Irineo Lorenzo (Revista Mexicana de Ciencias Agrícolas, 2022)
The consequences of climate change on crops are a cause for concern, as they cannot adapt quickly to new pathogenic threats. This article reviews the global use of mathematical models in plant health during the 2000-2020 period, through Scopus and Google Scholar. The objective of this study is to show modeling and simulation as an option in crop protection against meteorological risks or variations that occur due to global warming. Mathematical modeling is not an end in itself but a tool that helps in decision making for the sustainable management of crops. The prediction of the risk of occurrence of a pest or disease favors the reduction of the use of pesticides, thus reducing economic losses and damage to the environment. On the other hand, the simulation or numerical solution of mathematical models allows the exploration of hypotheses, it is an invaluable means in the research, since it allows exploring possible future scenarios and finding options of management systems that will be necessary at some point. In Mexico, it is necessary to carry out research for the generation and implementation of mathematical models that allow a lower cost of production and less negative impact on human health and the environment.
Keywords: computation applied to plant health; decision making; disease management